2008
DOI: 10.1111/j.1462-5822.2007.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Muramylpeptide shedding modulates cell sensing of Shigella flexneri

Abstract: SummaryBacterial infections trigger the activation of innate immunity through the interaction of pathogenassociated molecular patterns (PAMPs) with pattern recognition molecules (PRMs). The nucleotidebinding oligomerization domain (Nod) proteins are intracellular PRMs that recognize muramylpeptides contained in peptidoglycan (PGN) of bacteria. It is still unclear how Nod1 physically interacts with PGN, a structure internal to the Gram-negative bacterial envelope. To contribute to the understanding of this proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 52 publications
5
77
0
Order By: Relevance
“…S3A) and PGN ( Fig. S3 B and C) in HEK 293 cells expressing TLR2 (i.e., BLPs) or hNod1 or hNod2 (i.e., PGN) (34). Then, LPSs were assessed in bone marrow-derived macrophages (BMDMs) in the presence or absence of Oxidized 1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphocholine (OxPAPC)C (40 μg/mL; Fig.…”
Section: Activation Of Nf-κb By Lps Extracted From Acellular and Intrmentioning
confidence: 99%
“…S3A) and PGN ( Fig. S3 B and C) in HEK 293 cells expressing TLR2 (i.e., BLPs) or hNod1 or hNod2 (i.e., PGN) (34). Then, LPSs were assessed in bone marrow-derived macrophages (BMDMs) in the presence or absence of Oxidized 1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphocholine (OxPAPC)C (40 μg/mL; Fig.…”
Section: Activation Of Nf-κb By Lps Extracted From Acellular and Intrmentioning
confidence: 99%
“…One possible explanation is that the Pdi-dependent ability of S. iniae to form longer chains reduces the efficiency of phagocytic uptake and clearance. Another possible explanation for this decreased survival is that deacetylation of S. iniae cell surface molecules introduces significant changes in molecular patterns that are otherwise easily recognized by the host immune system, thus allowing WT S. iniae to survive and persist in vivo (Arancibia et al, 2007;Nigro et al, 2008). In examining specific potential effectors of phagocytic killing, we have found no difference in the kinetics of the killing of WT and Dpdi by hydrogen peroxide (a component of the oxidative burst) and the cationic HSB AMP moronecidin.…”
Section: Discussionmentioning
confidence: 99%
“…3A). Indeed, it was shown that muramylpeptides shed by Shigella in epithelial cells are able to trigger Nod1-mediated NF-kB activation [18]. Muramylpeptides can be also generated in the cytosol after invasion by Gram-positive bacteria.…”
Section: Nod2-dependent Nf-kb and Mapks Activation Pathways In Responmentioning
confidence: 99%